1968
DOI: 10.1042/bj1080417
|View full text |Cite
|
Sign up to set email alerts
|

The effects of catabolic and anabolic steroids on amino acid incorporation by skeletal-muscle ribosomes

Abstract: 1. A method is described for the routine isolation of ribosomes from small quantities of skeletal muscle that have been homogenized with the Ultra-Turrax tissue disintegrator. 2. Ribosomes prepared by this method from rats receiving triamcinolone acetonide or rabbits receiving cortisone acetate show a marked fall in their ability to incorporate amino acids when compared with ribosomes from control animals. 3. This fall in activity can be partially prevented in rats by pretreating the animals with an anabolic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1970
1970
1997
1997

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…It was reported that atrophy induced by corticosteroid is due to accelerated break down and decreased synthesis of muscle protein [10][11][12] . Shoji, et al reported that corticosteroid inhibits intramuscular ATP synthesis in the pathogenesis of steroid myopathy 13) .…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that atrophy induced by corticosteroid is due to accelerated break down and decreased synthesis of muscle protein [10][11][12] . Shoji, et al reported that corticosteroid inhibits intramuscular ATP synthesis in the pathogenesis of steroid myopathy 13) .…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomes isolated from the predominantly white hind-limb muscles ofadult male rats have a decreased ability to incorporate amino acids into protein in vitro when the animals have previously been treated with the powerful catabolic agent triamcinolone acetonide (9a-fluoro-1l1l,21-dihydroxy-16ac,17ao-isopropylidenedioxypregna -1,4 -diene -3,20 -dione) (White, 1967;Bullock et al, 1968;Peters et al, 1970;Bullock et al, 1971). Similar results were obtained when rabbits were given cortisone (Bullock et aL, 1968). The ribosomal defect develops comparatively rapidly (4-6h) after the administration of Vol.…”
mentioning
confidence: 99%
“…The ribosomal defect develops comparatively rapidly (4-6h) after the administration of Vol. 127 the catabolic agent to rats (Peters et al, 1970) and can be fully or partially reversed by treating the animals with steroids that have an anabolic action (White, 1967;Bullock et al, 1968Bullock et al, , 1971. From this it would appear likely that the dysfunctional state of the ribosomes reflects events in the cell that are primary determinants of steroid-induced muscle catabolism.…”
mentioning
confidence: 99%
“…In each experiment ribosomes were isolated from five control animals (intact or castrated) and five drug-treated animals 12h after the administration of the drug. The amino acidincorporating ability in vitro of the ribosome preparation from each animal was measured over a 20min incubation period in the presence of diluted liver cell sap and energy (Bullock, White & Worthington, 1968). The method for the isolation of ribosomes was essentially as described previously (Peters, Richardson, Small &;White, 1970) except that 0.1 M-tris buffer was used in the homogenizing medium and treatment with amylase was omitted.…”
mentioning
confidence: 99%